Economic analysis of beekeeping enterprises producing chestnut honey Black Sea region in Turkiye - Polat, Murat; CevrImlI, Mustafa Bahadir; Mat, Burak; Akin, Ahmet Cumhur; Arikan, Mehmet Saltuk; TekIndal, Mustafa Agah (Taylor & Francis Ltd, 2023)
In the present study, we economically analyzed the enterprises producing chestnut honey in the TR82 region provinces of the Black Sea region of Turkey (Kastamonu, cankiri, and Sinop provinces). Face-to-face interviews were conducted to collect data from 74 small, medium, and largescale enterprises, and data were analyzed by simple random sampling. Furthermore, a backward regression model was developed to assess the input and output relationships in the enterprises. The average honey yield per hive was 4.06 kg. The statistically significant difference was found between scales and provinces in unit cost. The unit cost average of small-scale enterprises was statistically different from that of large-scale enterprises. A statistical difference was found between provinces in sales price and profit per hive (p < 0.05). The adjusted R2 value was found to be 0.865 for the regression model created with the variables affecting the unit cost. The lowest honey production cost (10.52 US$) was found in small-scale enterprises and the cankiri province (9.17 US$/kg), whereas the highest production cost (12.34 US$/kg) was found in large-scale enterprises and the Sinop province (12.38 US$/kg). The net profit per hive was calculated to be US$52.83 for small-scale enterprises and US$46.47 for medium and large scales. Thus, chestnut honey can be marketed as a geographically indicated product at a high price. However, the increased number of enterprises producing chestnut honey, along with a lack of professionalism and insufficient technical knowledge and interest, has raised production costs. These findings suggest that producers should be encouraged to reduce their unit costs to increase their profit.
Keywords: beekeeping; enterprise; Turkiye; chestnut honey; Black Sea region; >